IMPLEMENTING CONSTRUCTIVISM LEARNING THEORY IN ONLINE TUTORIAL - Benny A Pribadi; Anis Surtiani; Ichwan Ichwan (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
The advanced development of information and communication technologybrings a significant impact on the way of how human learn. The e-learning orInternet-based and online learning has been widely used in a variety of learning activities as a suplement to the conventional in-class learning, flipped classroom etc. The term e-learning refers to learning activities conducted by the use ofInternet. Universitas Terbuka (UT) utilizes e-learning program in the form of online tutorial. The online tutorial is basically a form of learning support provided by UT to facilitate student to learn. The online tutorial consists of three major learning activities including reading, discussion and assignment. During online tutorial student must complete the assigned activities and interaction with peers, tutor and digital learning resources. Online tutorial can be seen as an instrumental tool that provide an opportunity for students to expandhis/her knowledge and skills beyond the provided printed and digital module. Tutors should be able to design online learning programs that can be used to facilitate students in expanding their knowledge and skills. The purpose of this study is to elaborate conceptually the use of constructivism learning theory in online tutorial of the open and distance learning higher institution.